Active surveillance of pathogens from ticks collected in New York State suburban parks and schoolyards. (22nd July 2020) - Yuan, Qin; Llanos‐Soto, Sebastian G.; Gangloff‐Kaufmann, Jody L.; Lampman, Joellen M.; Frye, Matthew J.; Benedict, Meghan C.; Tallmadge, Rebecca L.; Mitchell, Patrick K.; Anderson, Renee R.; Cronk, Brittany D.; Stanhope, Bryce J.; Jarvis, Ava R.; et al.
Abstract: Schoolyards and suburban parks are two environments where active tick surveillance may inform local management approaches. Even in a state such as New York with a robust active tick surveillance programme operated by the state Department of Health, these settings are not routinely covered. The goal of this study was to highlight the importance of active surveillance for tick‐borne pathogens by describing their prevalence in ticks collected from schoolyards and suburban parks and to guide the use of integrated pest management in these settings. Tick dragging was performed in three regions of New York State: Long Island, the Lower Hudson Valley and the Capital Region. A total of 19 schoolyards and 32 parks were sampled. The location, habitat and weather at the time of tick collection were recorded. Ticks were speciated and tested for the presence of 17 pathogens with a novel application of nanoscale real‐time PCR. The causative agents of Lyme disease, anaplasmosis, babesiosis and Powassan virus disease were all detected from Ixodes scapularis in various sites throughout the capital region and south‐eastern counties of New York state. The most common agent detected was Borrelia burgdorferi, and coinfection rates were as high as 36%. This surveillance study also captured the first of the invasive Asian longhorned tick species, Haemaphysalis longicornis, in New York state (collected 2 June 2017). Results from this study highlight the importance of collaborative efforts and data sharing for improvement of surveillance for tick‐borne disease agents.